IoT Based Remote Patient Health Monitoring System - Ravi Kumar Sariki; Chandra Sekhar Rao T.; Venkata Suman Jami; Usha Rani B. (E3S Web of Conferences)
Regular health monitoring is essential for maintaining good health, but long hospital queues and the need for ambulatory monitoring in our fast-paced world underscore the necessity for a simple health monitoring system adaptable to various settings. This system addresses the increasing demand for monitoring primary health parameters, particularly among older individuals, where conventional healthcare infrastructure often falls short. To overcome these challenges, we propose a comprehensive health monitoring system leveraging Internet of Things (IoT) technology. By utilizing IoT, we can wirelessly capture and transmit health data, ensuring interoperability. Our system collects and transmits vital health parameters such as body temperature, blood pressure, pulse, and GPS location using an Arduino Board and Wi-Fi module for data processing and transmission, respectively. This approach allows for real-time data capture, analysis, and storage, with automatic alerts sent to healthcare professionals when critical conditions are detected. Overall, our system offers user-friendly health monitoring, timely intervention, and reduces the burden on overcrowded healthcare facilities.